Enemy of the state [compact disc, unabridged] - Mills, Kyle, 1966- (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2017)
With a non-aggression pact in place that keeps Saudi involvement in 9/11 quiet in exchange for oil, Mitch Rapp undergoes a covert mission as a traitor to keep the peace when evidence emerges that the Saudis are funding ISIS.